3D Carbon-Electrode Dielectrophoresis for Enrichment of a Small Cell Population from a Large Sample Volume. (27th April 2016) - Islam, Monsur; Natu, Rucha; Larraga-Martinez, Maria Fernanda; Dávila, Guillermo Contreras; Martinez-Duarte, Rodrigo
Abstract : Isolation and enrichment of cells from a diluted sample is necessary for different clinical applications. Here we have demonstrated the use of 3D carbon electrode dielectrophoresis (DEP) to process a diluted yeast sample featuring concentration as low as 10 2 cells/ml. The yeast cells in the sample were first trapped on carbon electrodes by implementing positive DEP force and then released and concentrated in a small volume of clean buffer. The maximum limit of the cell trapping for our device was found to be around 4000 cells. Using 10 µl/min, an enrichment of 154.2 ± 23.7 folds was achieved, where sample of 10 2 cells/ml concentration was enriched up to 4 X 10 4 cells/ml. Upon increasing the flow rate up to 30 µl/min, the enrichment dropped down to 18.4 ± 4 folds due to the increase of drag force, though the enriched concentration around 10 4 cells/ml was still achieved.